Aantifraud Control Programs - A Holistic Approach towards The Prevention and Detection of Fraud - Gkarozis, Spyros (2005)
Antifraud control programs have become the cornerstone in the fight against the prevention and detection of fraud. Indirectly the call and the necessity for their existence come from several sources. The lessons that we all learned from the big corporate scandals; the examination of the root causes of fraud; new possible approaches towards the prevention and detection of fraud; the role of boards today in the fight against economic crime; the urgent need for transparency and accountability in the global economic system. Additionally, the examination of fraud's nature, classification, the collateral cost involved, and the existing framework from related authorities, regulatory bodies, legislation efforts, governmental or private efforts, are showing very clearly the necessity for the existence of the antifraud control programs. Two factors that play a vital role during the creation and the implementation of such a control program are corporate governance and organizational culture. Following the examination of all the above a proposed model of what an antifraud control program should include as far as for its components is suggested. Furthermore, vital factors for the appropriate function of each component are examined. Moreover, an effort is taking place for the pros and cons of such a program to be identified and highlighted. The degree of integration in-between the model's components and the equal gravity given between them also seem to play a crucial role for their success.